Single Mothers Parenting Style In Adolescent Development: A Pilot Study - Ika Indrawaty Hamzah; Fauziah Md jaafar (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
This study aims to understand the single mother parenting style in adolescent development. This pilot study involved three single mothers in Wajo District, South Sulawesi, Indonesia. Criteria single mothers were selected based on the following criteria: (1) those who are divorced, widow, separated or single parenting, and abandoned by her husband for two years which do not provide for sufficient; (2) they are the mother of their own child, and (3) they have children aged 13-15 years old. The study participants were coded to represent single mothers (SM), consisting of SM1-PS, SM2-PS, dan SM3-PS. Data were collected through in-depth interviews with the participants. The interview session takes about 20-30 minutes for each participant and interviews are recorded by voice recording device. The data gathered from semi-structured interviews were transcribed. The data analyzed using N-vivo 11 software. The results reported two main themes are: 1) the relationship between single mother and the child, with sub-theme are: communication; 2) the single mother ways in parenting style, with sub-themes: motivation, setting rules, solving the problem, supporting children’s activities, respecting children’s opinions. Conclusion: The relationships between single mother and their child as well that is supported by communication with the mother. The ways that single mothers do in parenting style applies motivation, setting rules, solving the problem, supporting children’s activities, respecting children’s opinions. Those ways are more like authoritative parenting style. In addition, the single mothers who use corporal punishment by hitting children are more likely to cause children to run away from home and afraid to go home. In addition, the mother is firm in showing her decision to be followed by the child and no one can change it. The ways that single mothers do are more likely to be authoritarian style.